Semi-cured adhesive insulating film, preparation method, application and use method thereof

Through the semi-cured bonded insulating film with a three-layer composite structure, combined with nanospherical boron nitride powder and aluminum nitride powder, the installation problem of traditional thermally conductive insulating media between power transistors and radiators is solved, and efficient heat dissipation and simplicity are achieved. Installation and high mechanical strength, suitable for high density power supply design.

CN119242193APending Publication Date: 2025-01-03SHENZHEN UNION TENDA TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411382521.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The installation of traditional thermally conductive insulating medium between power transistors and heat sinks has problems such as limited insulation distance, fragility, large space occupancy, high cost and difficult design, which is difficult to meet the needs of high-density power supply design.

Method used

The semi-cured adhesive insulating film adopts a three-layer composite structure, including two upper and lower layers of organic silicone layer filled with thermal filler and a middle polyimide film, through high viscosity liquid silicone rubber, nanospherical boron nitride powder and nitride Aluminum powder and other components are composed of microcapsule platinum catalysts to form an efficient thermally conductive adhesive layer, and bonding is achieved through pressure and heat treatment.

Benefits of technology

It realizes efficient heat dissipation, simple installation, high insulation performance, low cost and high mechanical strength, and is suitable for high-density power supply design, reducing material costs and design difficulties, and improving service life and environmental adaptability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242193A_ABST
    Figure CN119242193A_ABST
Patent Text Reader

Abstract

The invention discloses a semi-cured adhesive insulating film, a preparation method, application and a use method thereof. The semi-cured adhesive insulating film comprises an upper organic silica gel layer, a lower organic silica gel layer and a middle polyimide film, wherein the upper organic silica gel layer and the lower organic silica gel layer are filled with heat-conducting filler; the organic silica gel layer is prepared from the following components in parts by weight: 6 to 8 parts of high-viscosity liquid organic silicon rubber, 2 to 3 parts of low-viscosity liquid organic silicon rubber, 0.5 to 0.8 part of hydrogen-containing silicone oil, 0.1 to 0.5 part of an inhibitor, 0.1 to 0.2 part of a platinum catalyst, 0.1 to 0.3 part of a silane coupling agent, 0.1 to 0.3 part of an organic silicon tackifier and 10 to 20 parts of nano spherical boron nitride powder; and 20-40 parts of aluminum nitride powder. The semi-cured insulating adhesive film is prepared by compositely filling the organic silica gel layers of the heat-conducting filler on the two surfaces of the polyimide film, and is small in occupied space, simple in assembly process, high in insulating reliability and low in use cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal conductive materials, and in particular to a semi-cured adhesive insulating film, a preparation method, an application and a use method thereof. Background Art

[0002] With the explosive growth of new energy vehicles, there is a huge demand for various high-performance thermal conductive materials. Among them, various power transistors (MOSFET, IGBT) are the core components of automotive power supply devices. When the power supply is working, the power transistor switches frequently, withstands high voltage, high current and generates a lot of heat. In order to ensure stable and reliable operation of the power supply, the power tube must be installed on radiators of various shapes, and ensure that the power tube and the radiator are insulated and the interface thermal resistance between the power tube / radiator is as small as possible. Insulation and heat dissipation problems may cause transistor breakdown and short circuit, overheating and explosion of the tube, and then cause the entire power supply device to explode, and in severe cases burn out.

[0003] The traditional solution to the above problems is to place a thermally conductive insulating medium (Al203 ceramic sheet + thermally conductive silicone grease, thermally conductive insulating silicone cloth, thermally conductive phase change film) between the power tube and the heat sink, and press the power tube against the surface of the heat sink by mechanical fastening (direct screw locking, screw + pressure strip / pressure block locking, spring clip clamping). For example, patent CN201320293795.0 enhances the heat conduction between the heat dissipation aluminum block, the ceramic sheet, and the heat sink by applying thermally conductive silicone grease on both sides of the ceramic sheet, and fixes the transistor with a Z-shaped pressing sheet. This method has the problems of ceramic sheet fragility and thermal grease aging, and the Z-shaped pressing sheet mechanical fixing method takes up more space and is inconvenient to install. Patent CN202320958355.6 presses the transistor on the thermally conductive insulating sheet by a pressing piece, and the other side of the thermally conductive insulating sheet contacts the thermal block, and in this way assembles it into a transistor assembly. This method increases the structural cost of the pressing piece and occupies space, which is not conducive to high-density power supply design.

[0004] In summary, the traditional method of adding a thermally conductive insulating medium between the power tube and the heat sink and fixing them mechanically has the following problems: 1. The insulation distance is limited, and it is difficult to meet the requirements of higher insulation levels; 2. Screw installation can easily cause the insulating medium and the power tube to be squeezed and damaged; 3. It takes up a large space and is difficult to meet the requirements of high-density power supply design; 4. Additional fixed structural parts increase material costs and design difficulty.

[0005] The use of the ceramic sheet prepared by Chinese patent CN202110778056.X requires the application of thermal grease to fill the interface gaps, and the ceramic sheet is at risk of being fragile; the thermally conductive insulating sheet prepared by Chinese patent 201810383249.3 requires additional structural parts to fix the transistors and heat sink when used.

[0006] In solid-state physics, phonons are the quantized form of lattice vibrations. Phonon transmission refers to the process of transferring lattice vibration energy in a crystal. Phonon modes are divided into four categories: extended mode, localized mode, partially extended mode, and isolated mode. In extended mode and localized mode, the phonons between the two lattices are strongly correlated, so that the phonons on one side scatter and reach the other side, forming a phonon bridge, which helps to improve the thermal conductivity between fillers; while the partially extended mode and isolated mode contribute little to the interface thermal conductivity.

[0007] Experiments have found that the phonon modes of AlN / BN and AlN / Al2O3 are very different, resulting in a large difference in thermal conductivity. It is easier to form phonon bridges between nitrides, and the phonons between aluminum nitride and boron nitride are more likely to be in extended and localized modes. Phonons undergo inelastic scattering to exchange energy and promote heat transfer. At the same time, spherical boron nitride is easy to form a vertical serial arrangement, which reduces the reflection and scattering of phonons, greatly reduces thermal resistance, and improves thermal conductivity. Summary of the invention

[0008] In view of the problems existing in the prior art, the present invention provides a semi-cured adhesive insulating film, a preparation method, an application and a use method thereof.

[0009] In order to achieve the above object, the present invention provides a semi-cured adhesive insulating film, which is a three-layer composite structure, including: upper and lower layers of organic silicone layers filled with thermal conductive fillers, and a polyimide film in the middle.

[0010] Preferably, the organic silica gel layer is composed of the following components in parts by weight:

[0011] 6-8 parts by weight of high-viscosity liquid silicone rubber, 2-3 parts by weight of low-viscosity liquid silicone rubber, 0.5-0.8 parts by weight of hydrogenated silicone oil, 0.1-0.5 parts by weight of inhibitor, 0.1-0.2 parts by weight of platinum catalyst, 0.1-0.3 parts by weight of silane coupling agent, 0.1-0.3 parts by weight of silicone tackifier, 10-20 parts by weight of nano-spherical boron nitride powder, 20-40 parts by weight of aluminum nitride powder, and 50-100 parts of organic solvent; among them, nano-spherical boron nitride is a new type of nanomaterial, prepared by high-temperature and high-pressure synthesis technology, with the characteristics of high melting point, good thermal stability and chemical stability; compared with flake boron nitride, spherical boron nitride has a smaller specific surface area, can bring higher powder filling amount, and improve thermal conductivity. At the same time, compared with flake boron nitride, it is easy to form a vertical serial arrangement, which is more conducive to reducing the thermal resistance of thermal interface materials and improving thermal conductivity.

[0012] Preferably, the high-viscosity liquid silicone rubber is selected from one or more of double-terminal vinyl silicone oil, single-terminal vinyl silicone oil, side-chain vinyl silicone oil, and MQ vinyl silicone oil with a viscosity ranging from 100,000 to 800,000 cs.

[0013] Preferably, the low-viscosity liquid silicone rubber is selected from one or more of double-terminal vinyl silicone oil, single-terminal vinyl silicone oil and side-chain vinyl silicone oil with a viscosity ranging from 50 cs to 500 cs.

[0014] Preferably, the hydrogen-containing silicone oil is selected from one or more of methyl-terminated side hydrogen silicone oil, double-terminated hydrogen silicone oil, end-side hydrogen silicone oil, and phenyl-side hydrogen silicone oil having a hydrogen content in the range of 0.05-0.18%.

[0015] Preferably, the inhibitor is 3,7,11-trimethyldodecyne-3-ol;

[0016] The platinum catalyst is a microcapsule type platinum catalyst, the capsule particle size is 50 μm, the softening point is 120° C., and the encapsulated concentration of the chloroplatinic acid catalyst is 2000 ppm;

[0017] The silane coupling agent is selected from one or more of trimethoxysilane, vinyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-aminopropyl triethoxysilane, and N-β-aminoethyl-γ-aminopropyl trimethoxysilane.

[0018] Preferably, the organosilicon tackifier is selected from one of a silicon boron tackifier and an MQ silicone resin tackifier;

[0019] The nano-spherical boron nitride powder is: spherical boron nitride powder with a particle size of 100nm or spherical boron nitride powder with a particle size of 500nm;

[0020] The aluminum nitride powder is: spherical aluminum nitride powder with a particle size of 1 μm or spherical aluminum nitride powder with a particle size of 5 μm.

[0021] The organic solvent is petroleum ether, cyclohexane or ethanol.

[0022] The present invention provides a method for preparing a semi-cured insulating adhesive film, comprising the following steps:

[0023] Step S1: high-viscosity liquid silicone rubber, low-viscosity liquid silicone rubber, hydrogen-containing silicone oil, inhibitor, silane coupling agent, tackifier, and organic solvent are mixed together in proportion and stirred evenly;

[0024] Step S2: Add spherical boron nitride powder and aluminum nitride powder, put into a homogenizer and stir at 2000 rpm for 10 minutes;

[0025] Step S3: finally, add a microcapsule platinum catalyst, put it into a homogenizer and stir it at 1500 rpm in vacuum for 5 minutes to obtain a thermally conductive adhesive silica gel slurry;

[0026] Step S4: Use an adjustable scraper, adjust the scraper height to 150 μm, and the coating speed to 3 m / min, to coat the thermally conductive adhesive silicone slurry on the 25 μm polyimide film, and dry it at 80° C. for 5 min to make the silicone layer reach a semi-cured state;

[0027] Step S5: coating the back of the polyimide film in the same manner and drying to obtain a semi-cured insulating adhesive film;

[0028] Step S6: Finally, the upper and lower surfaces of the semi-cured insulating adhesive film are covered with PET release films and stored in a refrigerator at 0-10°C.

[0029] Preferably, the PET release film is one of a silicone release film, a non-silicone release film, and a fluorine release film.

[0030] Preferably, the prepared semi-cured insulating adhesive film is applied to a power transistor to achieve bonding between a heat sink and a power transistor.

[0031] The present invention also provides a method for using the semi-cured adhesive insulating film, comprising the following steps:

[0032] Step X1: Place and position the heat sink, semi-cured adhesive insulating film, and power tube in sequence;

[0033] Step X2: Apply 100-140 psi pressure to the insulating film for 10 seconds, so that the insulating film deforms under pressure and fills the gap between the power tube and the heat sink interface, effectively reducing the interface thermal resistance;

[0034] Step X3: Heat the insulating film to 150°C and maintain for 15 minutes to allow the organic silicone layer to undergo a cross-linking reaction to achieve bonding between the heat sink and the power tube. When the temperature exceeds 120°C, the platinum catalyst capsule softens and releases the platinum catalyst to initiate hydrosilylation polymerization, bonding and curing the MOS tube from top to bottom.

[0035] The technical solution of the present invention has the following beneficial effects:

[0036] The invention prepares a semi-cured insulating adhesive film by compounding an organic silica gel layer filled with a heat-conducting filler on both sides of a polyimide film. The semi-cured insulating adhesive film of the invention occupies a small space, has a simple assembly process, high insulation reliability and low use cost.

[0037] The present invention has high efficiency in heat dissipation: the semi-cured adhesive insulating film of the present invention adopts a three-layer composite structure, the upper and lower layers are organic silicone layers filled with thermal conductive fillers, and the middle layer is a polyimide film. This structural design effectively improves the heat conduction efficiency, reduces the interface thermal resistance between the power transistor and the heat sink, and thus improves the heat dissipation performance.

[0038] The present invention has the advantages of simple installation: using the semi-cured adhesive insulating film of the present invention, it is only necessary to place and position the heat sink, the semi-cured adhesive insulating film, and the power transistor in sequence, and then apply a pressure of 100-140psi for 10 seconds, and then heat to 150°C and keep for 15 minutes to achieve the bonding of the heat sink and the power transistor. This method simplifies the installation process, improves production efficiency, and reduces labor intensity.

[0039] The present invention has high insulation performance: the polyimide film as the middle layer provides excellent electrical insulation performance, ensures electrical isolation between the power transistor and the heat sink, and avoids the risks of short circuit and breakdown.

[0040] The invention has high mechanical strength: the organic silica gel layer forms a stable bond after curing, and the combination with the polyimide film provides good mechanical strength, thereby ensuring the stability and reliability of the power transistor in various working environments.

[0041] The space utilization rate of the present invention is high: the semi-cured adhesive insulating film of the present invention has uniform thickness and occupies little space, which is conducive to the miniaturization and high-density installation of electronic equipment and meets the strict space requirements of modern electronic equipment.

[0042] The invention has low cost: the semi-cured adhesive insulating film of the invention eliminates the need for traditional mechanical fastening structural parts, reduces material cost and manufacturing cost, and simplifies the production process, which is conducive to reducing the overall cost.

[0043] The present invention has strong environmental adaptability: the organic silica gel layer has good high temperature resistance, low temperature resistance and aging resistance, so that the semi-cured adhesive insulating film of the present invention is suitable for various environmental conditions, including extreme temperature and humidity environments.

[0044] The invention has a long service life: since the semi-cured adhesive insulating film of the invention has excellent chemical stability and mechanical stability, it has a long service life, and reduces the frequency of maintenance and replacement.

[0045] It can be found from the solution of the present invention that the thermal resistance of AlN / Al2O3 is much higher than that of AlN / BN, indicating that the phonons between AlN / Al2O3 exist in partial extended modes and isolated modes, and the phonon scattering of the AlN lattice fails to reach the Al2O3 lattice, and no phonon bridge can be formed, resulting in low heat transfer efficiency; at the same time, the adhesive film with nano-spherical boron nitride powder has a higher breakdown voltage than the spherical alumina powder, which improves the insulation performance of the adhesive film; MQ silicone resin tackifier significantly improves the bonding shear strength, indicating that the MQ siloxane functional group can react with the active groups (such as hydroxyl groups, amino groups, etc.) on the surface of the substrate to form a more stable bonding layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 It is a schematic structural diagram of the semi-cured adhesive insulating film of the present invention. DETAILED DESCRIPTION

[0047] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0048] Example 1

[0049] Reference Figure 1 The present invention provides a semi-cured adhesive insulating film, which is a three-layer composite structure, including: an upper and lower organic silicone layer filled with thermal conductive fillers, and a polyimide film in the middle.

[0050] The present invention also provides a method for preparing a semi-cured adhesive insulating film, wherein the organic silicone layer is prepared from the following raw materials in parts by weight:

[0051] 100000cs double-terminated vinyl silicone oil 8 parts;

[0052] 2 parts of 50cs double-terminated vinyl silicone oil;

[0053] 0.5 part of phenyl hydrogen silicone oil;

[0054] 0.2 parts of 3,7,11-trimethyldodecyne-3-ol;

[0055] 0.1 part of microcapsule platinum catalyst;

[0056] 0.3 parts of dimethoxydiphenylsilane;

[0057] 0.1 part of silicon boron tackifier;

[0058] 30 parts of 5μm spherical aluminum nitride powder;

[0059] 15 parts of 100nm spherical boron nitride powder;

[0060] 50 parts of cyclohexane;

[0061] Preparation of organic silica gel layer: 8 parts of 100000cs double-terminal vinyl silicone oil, 2 parts of 50cs double-terminal vinyl silicone oil, 0.5 parts of phenyl hydrogen silicone oil, 0.2 parts of 3,7,11-trimethyldodecyne-3-ol, 0.3 parts of dimethoxydiphenylsilane, 0.1 parts of silicon boron tackifier, and 50 parts of cyclohexane are added together and stirred evenly; then 30 parts of 5μm spherical aluminum nitride powder and 15 parts of 100nm spherical boron nitride powder are added, and the mixture is placed in a homogenizer and stirred at 2000rpm in vacuum for 10 minutes; finally, 0.1 parts of microcapsule platinum catalyst are added, and the mixture is placed in a homogenizer and stirred at 1500rpm in vacuum for 5 minutes to obtain thermal conductive adhesive silica gel slurry;

[0062] Preparation of semi-cured adhesive insulating film: Use an adjustable scraper, adjust the scraper height to 150μm, and the coating speed to 3m / min. Apply the thermal conductive adhesive silicone slurry on the 25μm polyimide film, and dry it at 80℃ for 5min. The silicone layer reaches a semi-cured state. Apply the back of the polyimide film in the same way and dry it to obtain a semi-cured insulating adhesive film. Finally, cover the upper and lower surfaces with 50μm PET fluorine release film and store it in a refrigerator at 0-10℃.

[0063] Use semi-cured adhesive insulating film for power transistors: when using, peel off the release film, place it between MOS tubes, apply 100-140PSI pressure, heat and cure at 150℃ for 30min. When the temperature exceeds 120℃, the capsule of platinum catalyst softens, releasing platinum catalyst to initiate silane addition polymerization, and the MOS tube is bonded and cured from top to bottom.

[0064] Example 2

[0065] Reference Figure 1 The present invention provides a semi-cured adhesive insulating film, which is a three-layer composite structure, including: an upper and lower organic silicone layer filled with thermal conductive fillers, and a polyimide film in the middle.

[0066] The present invention also provides a method for preparing a semi-cured adhesive insulating film, wherein the organic silicone layer is prepared from the following raw materials in parts by weight:

[0067] 800000cs double-terminated vinyl silicone oil 8 parts;

[0068] 2 parts of 50cs double-terminated vinyl silicone oil;

[0069] 0.5 part of hydrogen silicone oil on the end side;

[0070] 0.2 parts of 3,7,11-trimethyldodecyne-3-ol;

[0071] 0.1 part of microcapsule platinum catalyst;

[0072] 0.3 parts of dimethoxydiphenylsilane;

[0073] MQ silicone resin tackifier 0.2 parts;

[0074] 30 parts of 5μm spherical aluminum nitride powder;

[0075] 15 parts of 100nm spherical boron nitride powder;

[0076] Ethanol 70 parts;

[0077] Preparation of organic silica gel layer: add 8 parts of 800000cs double-terminal vinyl silicone oil, 2 parts of 50cs double-terminal vinyl silicone oil, 0.5 parts of end-side hydrogenated silicone oil, 0.2 parts of 3,7,11-trimethyldodecene-3-ol, 0.3 parts of dimethoxydiphenylsilane, 0.2 parts of silicon MQ silicone resin thickener, and 70 parts of ethanol together and stir evenly; then add 30 parts of 5μm spherical aluminum nitride powder and 15 parts of 100nm spherical boron nitride powder, put into a homogenizer and stir at 2000rpm in vacuum for 10 minutes; finally, add 0.1 parts of microcapsule platinum catalyst, put into a homogenizer and stir at 1500rpm in vacuum for 5 minutes to obtain thermal conductive adhesive silica gel slurry.

[0078] Preparation of semi-cured adhesive insulating film: Use an adjustable scraper, adjust the scraper height to 150μm, and the coating speed to 3m / min, and apply the thermal conductive adhesive silicone slurry on the 25μm polyimide film, and dry it at 80℃ for 5min, so that the silicone layer reaches a semi-cured state; apply the back of the polyimide film in the same way and dry it to obtain a semi-cured insulating adhesive film. Finally, cover the upper and lower surfaces with 50μm PET fluorine release film and store it in a refrigerator at 0-10℃.

[0079] Use semi-cured adhesive insulating film for power transistors: peel off the release film, place between MOS tubes, apply 100-140PSI pressure, and heat and cure at 150℃ for 30min. When the temperature exceeds 120℃, the capsule of platinum catalyst softens, releasing platinum catalyst to initiate silane addition polymerization, and the MOS tube is bonded and cured.

[0080] Example 3

[0081] Reference Figure 1 The present invention provides a semi-cured adhesive insulating film, which is a three-layer composite structure, including: an upper and lower organic silicone layer filled with thermal conductive fillers, and a polyimide film in the middle.

[0082] The present invention also provides a method for preparing a semi-cured adhesive insulating film, wherein the organic silicone layer is prepared from the following raw materials in parts by weight:

[0083] 100000cs double-terminated vinyl silicone oil 8 parts;

[0084] 2 parts of 50cs double-terminated vinyl silicone oil;

[0085] 0.5 part of phenyl hydrogen silicone oil;

[0086] 0.2 parts of 3,7,11-trimethyldodecyne-3-ol;

[0087] 0.1 part of microcapsule platinum catalyst;

[0088] 0.3 parts of dimethoxydiphenylsilane;

[0089] 0.1 part of silicon boron tackifier;

[0090] 30 parts of 5μm spherical aluminum nitride powder;

[0091] 15 parts of 100nm quasi-spherical aluminum oxide powder;

[0092] 50 parts of cyclohexane;

[0093] Preparation of organic silica gel layer: add 8 parts of 100000cs double-terminal vinyl silicone oil, 2 parts of 50cs double-terminal vinyl silicone oil, 0.5 parts of phenyl hydrogen silicone oil, 0.2 parts of 3,7,11-trimethyldodecene-3-ol, 0.3 parts of dimethoxydiphenylsilane, 0.1 parts of silicon boron thickener, and 50 parts of cyclohexane together and stir evenly; then add 30 parts of 5μm spherical aluminum nitride powder and 15 parts of 100nm quasi-spherical alumina powder, put into a homogenizer and stir at 2000rpm in vacuum for 10 minutes; finally, add 0.1 parts of microcapsule platinum catalyst, put into a homogenizer and stir at 1500rpm in vacuum for 5 minutes to obtain thermal conductive adhesive silica gel slurry.

[0094] Preparation of semi-cured adhesive insulating film: Use an adjustable scraper, adjust the scraper height to 150μm, and the coating speed to 3m / min. Apply the thermal conductive adhesive silicone slurry on the 25μm polyimide film, dry it at 80℃ for 5min, and the silicone layer reaches a semi-cured state; apply the back of the polyimide film in the same way and dry it to obtain a semi-cured insulating adhesive film. Finally, cover the upper and lower surfaces with 50μm PET non-silicon release film and store it in a refrigerator at 0-10℃.

[0095] Use semi-cured adhesive insulating film for power transistors: when using, peel off the release film, place it between MOS tubes, apply 100-140PSI pressure, and heat and cure at 150℃ for 30min; when the temperature exceeds 120℃, the capsule of the platinum catalyst softens, releasing the platinum catalyst to initiate silane addition polymerization, and the MOS tubes are bonded and cured from top to bottom.

[0096] Example 4

[0097] Reference Figure 1The present invention provides a semi-cured adhesive insulating film, which is a three-layer composite structure, including: an upper and lower organic silicone layer filled with thermal conductive fillers, and a polyimide film in the middle.

[0098] The present invention also provides a method for preparing a semi-cured adhesive insulating film, wherein the organic silicone layer is prepared from the following raw materials in parts by weight:

[0099] 100000cs double-terminated vinyl silicone oil 8 parts;

[0100] 2 parts of 50cs double-terminated vinyl silicone oil;

[0101] 0.5 part of phenyl hydrogen silicone oil;

[0102] 0.2 parts of 3,7,11-trimethyldodecyne-3-ol;

[0103] 0.1 part of microcapsule platinum catalyst;

[0104] 0.3 parts of dimethoxydiphenylsilane;

[0105] MQ silicone resin tackifier 0.2 parts;

[0106] 30 parts of 5μm spherical aluminum nitride powder;

[0107] 15 parts of 100nm spherical boron nitride powder;

[0108] 50 parts of cyclohexane;

[0109] Prepare the organic silica gel layer: add 8 parts of 100000cs double-terminal vinyl silicone oil, 2 parts of 50cs double-terminal vinyl silicone oil, 0.5 parts of phenyl hydrogen silicone oil, 0.2 parts of 3,7,11-trimethyldodecyne-3-ol, 0.3 parts of dimethoxydiphenylsilane, 0.2 parts of MQ silicone resin tackifier, and 50 parts of cyclohexane and stir evenly; then add 30 parts of 5μm spherical aluminum nitride powder and 15 parts of 100nm spherical boron nitride powder, put into a homogenizer and stir at 2000rpm in vacuum for 10 minutes. Finally, add 0.1 parts of microcapsule platinum catalyst, put into a homogenizer and stir at 1500rpm in vacuum for 5 minutes to obtain thermal conductive adhesive silica gel slurry;

[0110] Preparation of semi-cured adhesive insulating film: Use an adjustable scraper, adjust the scraper height to 150μm, and the coating speed to 3m / min, and apply the thermal conductive adhesive silicone slurry on the 25μm polyimide film, and dry it at 80℃ for 5min, so that the silicone layer reaches a semi-cured state; apply the back of the polyimide film in the same way and dry it to obtain a semi-cured insulating adhesive film, and finally cover the upper and lower surfaces with 50μm PET fluorine release film and store it in a refrigerator at 0-10℃.

[0111] Use semi-cured adhesive insulating film for power transistors: peel off the release film, place between MOS tubes, apply 100-140PSI pressure, and heat and cure at 150℃ for 30min. When the temperature exceeds 120℃, the capsule of platinum catalyst softens, releasing platinum catalyst to initiate silane addition polymerization, and the MOS tube is bonded and cured.

[0112] The following table 1 is the performance comparison results of Examples 1-4:

[0113] Table 1

[0114] project Example 1 Example 2 Example 3 Example 4 Thickness mm 0.19 0.19 0.19 0.19 Thermal resistance ℃*cm2 / W 2.17 2.32 4.42 2.18 Breakdown voltage kV 6.5 7.0 4.0 6.4 Shear strength MPa 3.1 3.3 3.1 3.5

[0115] As shown in Table 1, comparing Example 1 and Example 3, it can be found that the thermal resistance of AlN / Al2O3 is much higher than that of AlN / BN, indicating that the phonons between AlN / Al2O3 exist in partial extended modes and isolated modes, and the phonon scattering of the AlN lattice fails to reach the Al2O3 lattice, and the phonon bridge cannot be formed, resulting in low heat transfer efficiency. At the same time, the anti-breakdown voltage of the adhesive film with nano-spherical boron nitride powder is higher than that of spherical aluminum oxide powder, which improves the insulation performance of the adhesive film.

[0116] By comparing Example 1 and Example 4, it can be found that the MQ silicone resin tackifier significantly improves the bonding shear strength, indicating that the MQ siloxane functional group can react with the active groups (such as hydroxyl, amino, etc.) on the surface of the substrate to form a more stable bonding layer.

[0117] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A semi-cured adhesive insulating film, characterized in that: The semi-cured adhesive insulating film is a three-layer composite structure, including: upper and lower layers of organic silicone layers filled with thermal conductive fillers, and a polyimide film in the middle.

2. The semi-cured adhesive insulating film according to claim 1, characterized in that: The organic silica gel layer is composed of the following components in parts by weight: 6-8 parts by weight of high-viscosity liquid silicone rubber, 2-3 parts by weight of low-viscosity liquid silicone rubber, 0.5-0.8 parts by weight of hydrogenated silicone oil, 0.1-0.5 parts by weight of inhibitor, 0.1-0.2 parts by weight of platinum catalyst, 0.1-0.3 parts by weight of silane coupling agent, 0.1-0.3 parts by weight of silicone tackifier, 10-20 parts by weight of nano-spherical boron nitride powder, 20-40 parts by weight of aluminum nitride powder, and 50-100 parts of organic solvent.

3. The semi-cured adhesive insulating film according to claim 2, characterized in that: The high-viscosity liquid organic silicone rubber is selected from one or more of double-terminal vinyl silicone oil, single-terminal vinyl silicone oil, side-chain vinyl silicone oil and MQ vinyl silicone oil with a viscosity ranging from 100,000 to 800,000 cs.

4. The semi-cured adhesive insulating film according to claim 2, characterized in that: The low-viscosity liquid organic silicone rubber is selected from one or more of double-terminal vinyl silicone oil, single-terminal vinyl silicone oil and side-chain vinyl silicone oil with a viscosity ranging from 50cs to 500cs.

5. The semi-cured adhesive insulating film according to claim 2, characterized in that: The hydrogen-containing silicone oil is selected from one or more of methyl-terminated side hydrogen silicone oil, double-terminated hydrogen silicone oil, end side hydrogen silicone oil, and phenyl side hydrogen silicone oil with a hydrogen content in the range of 0.05-0.18%.

6. The semi-cured adhesive insulating film according to claim 2, characterized in that: The inhibitor is 3,7,11-trimethyldodecyne-3-ol; The platinum catalyst is a microcapsule type platinum catalyst, the capsule particle size is 50 μm, the softening point is 120° C., and the encapsulated concentration of the chloroplatinic acid catalyst is 2000 ppm; The silane coupling agent is selected from one or more of trimethoxysilane, vinyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-aminopropyl triethoxysilane, and N-β-aminoethyl-γ-aminopropyl trimethoxysilane.

7. The semi-cured adhesive insulating film according to claim 2, characterized in that: The organosilicon tackifier is selected from one of a silicon boron tackifier and an MQ silicone resin tackifier; The nano-spherical boron nitride powder is: spherical boron nitride powder with a particle size of 100nm or spherical boron nitride powder with a particle size of 500nm; The aluminum nitride powder is: spherical aluminum nitride powder with a particle size of 1 μm or spherical aluminum nitride powder with a particle size of 5 μm. The organic solvent is petroleum ether, cyclohexane or ethanol.

8. A method for preparing a semi-cured insulating adhesive film, characterized in that: The steps include: Step S1: high-viscosity liquid silicone rubber, low-viscosity liquid silicone rubber, hydrogen-containing silicone oil, inhibitor, silane coupling agent, tackifier, and organic solvent are mixed together in proportion and stirred evenly; Step S2: Add spherical boron nitride powder and aluminum nitride powder, put into a homogenizer and stir at 2000 rpm for 10 minutes; Step S3: finally, add a microcapsule platinum catalyst, put it into a homogenizer and stir it at 1500 rpm in vacuum for 5 minutes to obtain a thermally conductive adhesive silica gel slurry; Step S4: Use an adjustable scraper, adjust the scraper height to 150 μm, and the coating speed to 3 m / min, to coat the thermally conductive adhesive silicone slurry on the 25 μm polyimide film, and dry it at 80° C. for 5 min to make the silicone layer reach a semi-cured state; Step S5: coating the back of the polyimide film in the same manner and drying to obtain a semi-cured insulating adhesive film; Step S6: Finally, the upper and lower surfaces of the semi-cured insulating adhesive film are covered with PET release films and stored in a refrigerator at 0-10°C.

9. The semi-cured insulating adhesive film according to any one of claims 1 to 7, or the semi-cured insulating adhesive film prepared by the preparation method of claim 8, which is applied to a power transistor to achieve bonding between a heat sink and a power transistor.

10. A method for using a semi-cured adhesive insulating film, wherein the semi-cured adhesive insulating film is any one of claims 1 to 7, or is prepared by the preparation method of claim 8, characterized in that: The following steps are involved: Step X1: Place and position the heat sink, semi-cured adhesive insulating film, and power tube in sequence; Step X2: Apply 100-140 psi pressure to the insulating film for 10 seconds, so that the insulating film deforms under pressure and fills the gap between the power tube and the heat sink interface, effectively reducing the interface thermal resistance; Step X3: Heat the insulating film to 150°C and keep it for 15 minutes to allow the organic silicone layer to undergo a cross-linking reaction to achieve bonding between the heat sink and the power tube.

Citation Information

Cited By

  • Single-component organic silicon hot laminating adhesive capable of being cured in segmented manner as well as preparation method and application of single-component organic silicon hot laminating adhesive

    CN121759152A